Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Pada 19 Kabupaten/Kota Provinsi Sumatera Barat Tahun 2018-2021 (International Forum of Researchers and Lecturers, 2023)
To achieve regional independence, local governments must be able to manage their resources efficiently and effectively. This can be realized by government financial performance. This study aims to examine the effect of economic growth, local revenue, and capital expenditure on government financial performance. The samples of this study were 19 regencies / cities of West Sumatra Province in 2018-2021 using the total sampling technique. The analysis method used is the panel data regression method. Based on the results of this study, it shows that economic growth has no effect on government financial performance, local revenue has a positive and significant effect on government financial performance, and capital expenditure has a negative and significant effect on government financial performance.